Bringing the Battle to Britain: Band of Brothers and Television Runaway Production in the UK. Issue 3 (July 2020) - Knox, Simone
Abstract : This article explores the development and pre-production history of the 2001 HBO mini-series Band of Brothers . It does so via a combination of original archive research (conducted at the BFI Reuben Library) and interviews with several industry figures with relevant professional experience, including John Barclay, the current Head of Recorded Media for the UK trade union Equity, and Roger Harrop, the former director of regional film commission Herts Film Link. Using these methodologies, the article identifies Band of Brothers as the first significant US runaway television production in the UK, and uncovers how this HBO programme came to benefit from British film tax relief. Here, close attention is paid to dubious practices concerning tax policy and contractual agreements for actors, especially Damian Lewis's pay. The article demonstrates the impact Band of Brothers has had on television production in the UK in terms of providing Equity with a useful precedent when negotiating for subsequent international productions such as Game of Thrones (2011–19). Band of Brothers offers important and timely lessons to be learned, especially given the recent growth of US television runaway productions in the UK.